2017
DOI: 10.1177/1403494816685936
|View full text |Cite
|
Sign up to set email alerts
|

Ignorance is not bliss: The effect of systematic information on immigrants’ knowledge of and satisfaction with the Danish healthcare system

Abstract: Knowledge of the healthcare system is necessary for optimal healthcare-seeking behaviour. The results may form the basis of national and international changes in immigrant reception and optimise immigrants' contact with the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Healthcare education or written information had no measurable effect on participants’ actual healthcare use; both intervention groups and the control group made a somewhat similar decreased use of GPs, ERs, specialist doctors, hospital and outpatient hospital visits in the year after the intervention, except for use of dental care which remained stable across the groups. Findings from this study indicate that increased knowledge of access to the healthcare system [ 4 ] has only limited or no effect on healthcare-seeking behaviour, and actual healthcare use was not shown to be affected during the following year. A key message from this study is, therefore, that we have shown that it is possible to make interventions that modify some kinds of hypothetical healthcare-seeking behavior.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Healthcare education or written information had no measurable effect on participants’ actual healthcare use; both intervention groups and the control group made a somewhat similar decreased use of GPs, ERs, specialist doctors, hospital and outpatient hospital visits in the year after the intervention, except for use of dental care which remained stable across the groups. Findings from this study indicate that increased knowledge of access to the healthcare system [ 4 ] has only limited or no effect on healthcare-seeking behaviour, and actual healthcare use was not shown to be affected during the following year. A key message from this study is, therefore, that we have shown that it is possible to make interventions that modify some kinds of hypothetical healthcare-seeking behavior.…”
Section: Discussionmentioning
confidence: 96%
“…Of the 1572 participants, 528 were lost to follow-up mainly due to longer school absence or leave at the time of the follow-up survey, and only an insignificant number (four persons at the intervention school in 2012) did not want to participate. The follow-up study population comprised 1039 persons and represented a response rate of 66.4% (a detailed description of follow-up study population can be found in [ 4 ]). The response rate in the Intervention Groups (69.2%) was slighter higher than in the Control Group (61.9%).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Incorporating health literacy in adult basic education curricula offers a promising method of building health literacy capacity within the community by leveraging existing infrastructure and resources. [3][4][5] The importance of doing so is reinforced by the high prevalence of low health literacy in developed countries (e.g. 60% of the adult Australian population 6 ), the disproportionate impact on culturally and linguistically diverse groups 6 , and the fact that lower health literacy is an independent predictor of poorer health outcomes.…”
Section: Introductionmentioning
confidence: 99%